FACTORY LEARNING MANAGEMENT IN GROWING THE ENTREPRENEURSHIP OF VOCATIONAL SCHOOL STUDENTS IN KARAWANG DISTRICT (Case Study at SMK Rismatek Karawang and SMK Lentera Bangsa Karawang) - Satata Sunggoro; Ulfiah; Hilman Farouq Ghoer; Usep Kosasih (AGUSPATI Research Institute, 2022)
This research is due to concerns in preparing a competent workforce according to the expectations of the business and industry world (DUDI), Vocational Schools need to make new breakthroughs, one of which is the Teaching Factory learning program so that students are more skilled, independent, competitive and entrepreneurial. The purpose of this study is to determine and analyze Teaching Factory Learning Management in Growing the Entrepreneurial Spirit of Vocational High School Students with qualitative methods. The results of this study reveal that: (1) Teaching Factory Learning Management Planning in Growing the Entrepreneurial Spirit of Vocational School Students, is in accordance with the needs of the Business/Industry World (DUDI) through link and match collaboration; (2). Organizing Teaching Factory Learning Management in Growing the Entrepreneurial Spirit of Vocational School Students, hierarchically the school principal has carried out an organization that can assist the implementation of entrepreneurial activities in accordance with the planned program; (3). Implementation of Teaching Factory Learning Management in Fostering the Entrepreneurial Spirit of Vocational School Students by forming a small team to assist the task of implementing entrepreneurial activities that are considered to have met the criteria; (4). Evaluation of Teaching Factory Learning Management in Developing the Entrepreneurial Spirit of Vocational School Students conducted by teachers on entrepreneurship activities that are carried out regularly and continue to make improvements and improvements to the learning process on a regular basis; (5). Supporting factors and inhibiting factors for Teaching Factory Learning Management in Fostering the Entrepreneurial Spirit of Vocational School Students where creative and innovative teachers have been able to develop production units, especially Honda motorcycle repair shops, while the constraint on budget allocation is still limited; (6). The concept of Principal Leadership through Teaching Factory Learning Management in Growing the Entrepreneurial Spirit of Vocational School Students, entrepreneurial attitudes have been reflected in students who are practicing industrial work, this can be seen from the ability of students to try something, do not feel satisfied quickly, dare to take risks, and compete to get the best results.